Evaluasi Pelaksanaan Program Desa Tangguh Bencana Desa Sambungrejo Kecamatan Grabag Kabupaten Magelang Tahun 2019 - Suryana, Ma'rif Nanang; Sriyono, Sriyono (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2021)
This study aims to determine the process of implementing a disaster resilient village program, determine the level of community participation in a disaster resilient village program and obstacles in the implementation of a disaster resilient village program Sambungrejo Village, Grabag District, Magelang Regency. The population in this study amounted to 653 households with a sample of 65 households. Data collection tools and techniques use documentation, questionnaires, and interviews. Data analysis techniques in this study were descriptive qualitative analysis and descriptive statistical analysis. The results showed that (1) The process of implementing a disaster resilient village program in 2019 Sambungrejo Village had not been carried out optimally, the achievement indicators for the implementation of a disaster resilient village program were included in the category of Resilient Village Disaster Primary Level, (2) The level of community participation in resilient village programs the disaster was classified as low with a score of 29.4, (3) Obstacles were found in the implementation of Disaster Resilient Village Programs in the form of low community capacity, lack of socialization disaster risk reduction, lack of carrying capacity of village governments and limited program budgets Penelitian ini bertujuan untuk mengetahui proses pelaksanaan program desa tangguh bencana, mengetahui tingkat partisipasi masyarakat terhadap program desa tangguh bencana dan hambatan dalam pelaksanaan program desa tangguh bencana Desa Sambungrejo, Kecamatan Grabag, Kabupaten Magelang. Populasi dalam penelitian ini berjumlah 653 KK dengan sampel sebanyak 65 KK. Alat dan teknik pengambilan data menggunakan dokumentasi, kuesioner, dan wawancara. Teknik analisis data dalam penelitian ini analisis deskriptif kualitatif dan analisis statistik deskriptif. Hasil penelitian menunjukan bahwa (1) Proses pelaksanaan program desa tangguh bencana Desa Sambungrejo Tahun 2019 belum terlaksana secara optimal, ketercapaian indikator pelaksanaan program desa tangguh bencana Desa Sambungrejo masuk dalam kategori Desa Tangguh Bencana Tingkat Pratama, (2) Tingkat partisipasi masyarakat terhadap program desa tangguh bencana tergolong rendah dengan skor 29,4, (3) Ditemukan hambatan dalam pelaksanaan Program Desa Tangguh Bencana Desa Sambungrejo berupa rendahnya kapasitas masyarakat, kurangnya sosialisasi pengurangan risiko bencana, kurangnya daya dukung pemerintah desa dan terbatasnya anggaran program.